The Phylogenetic Relationship Revealed Three New Wood-Inhabiting Fungal Species From Genus Trechispora - Zhao, Wei; Zhao, Chang-Lin (Frontiers in Microbiology, 2021)
Wood-inhabiting fungi play a significant role in wood degradation and the cycle of matter in the ecological system. In the present study, three new wood-inhabiting fungal species, T. bambusicola, T. fimbriata and T. fissurata spp. nov. are nested in Trechispora, which are proposed based on a combination of morphological features and molecular evidence. Sequences of ITS and nLSU regions of the studied samples were generated, and the phylogenetic analyses were performed with Maximum Likelihood, Maximum Parsimony and Bayesian Inference methods. The phylogenetic analyses inferred from ITS showed that T. bambusicola was sister to T. stevensonii; T. fimbriata grouped with T. nivea; T. fissurata grouped with T. echinospora. The phylogenetic tree based on ITS+nLSU sequences demonstrated that T. bambusicola formed a single lineage and then grouped with T. rigida and T. stevensonii. Trechispora fimbriata was sister to T. nivea. Trechispora fissurata grouped with T. thelephora.